Efeitos do pentobarbital sódico sobre o fluxo sanguíneo renal. Estudo experimental no cão - Braz, José Reinaldo Cerqueira [UNESP]; Colognesi, J. R.; Vianna, Pedro Thadeu Galvão [UNESP]; Yong, L. C. (My University, 1978)
In six dogs, previously anesthetized with sodium pentobarbital (30 mg/kg) for surgical preparation, catheterism and monitoring, the action of sodium pentobarbital (7,5 mg/kg) on renal flow was studied. Determinations of mean arterial pressure, venous pressure, cardiac rate, arterio-cava pressure gradient and renal arterial resistance were made. Pentobarbital doesn't change significantly the renal blood flow or any of the other parameters studied, with the exception of venous pressure in the inferior caval vein where the drug produces a significant fall.
Effects of sodium pentobarbital on the renal blood flow: Electromagnetic fluxometry. Experimental study in dogs
Keywords: pentobarbital; anesthesia; animal experiment; dog; electromagnetic flowmeter; intravenous drug administration; kidney; kidney blood flow; kidney function